An extensible framework for smart engineering simulation software: its architecture, implementation and applications - Zhang, C; MA, L (The International Journal of Multiphysics, 2014)
The industries are seeking smarter simulation tools to automatize the modeling work to alleviate the difficulties of using the numerical simulation techniques. The present work designs and implements an extensible framework to facilitate the development and deployment of the smart application-oriented simulation softwares. The kernel of the framework is the data management module which treats the various data in a unified approach. The geometry modeling module, the meshing module, the analysis module and the visualization module manipulate the data and the graphical user interface module assists in manipulating and displaying the data interactively. Two typical applications, i.e., the software for computing and analyzing the load-carrying capabilities of slew bearings and the software for designing the transmission tower, are presented for demonstrations.